Dos hábitos aos habitus: a (re)produção de sentidos no letramento escolar - Silva, Jemima Queiroz da (2014)
The school literacy has advocated tasks of reading and writing whose values are determined in the ideals of the skills that go beyond the boundaries of the school and reach the spaces of everyday life of individuals, guiding not only communication events, but alsoconceptions of the nature and potential of the person. Thus, the teaching of reading and writing has responded to the autonomousmodel of literacy, which assumes there is only one way of being literate, this, combined with the range of full citizenship rights and duties, and developing individual and collective progress. The slam of this practice is characterized as symbolic violence insofar as it excludes the possibility of the subject of other forms of relationship with reading and writing, creating arrays of behavior, habitus, marked by theacceptance of rules and sanctions of schooled literacy as neutral and universal. Thus, this study aims at analyzing, from the meanings assigned by a group of 11 students in the 9th year of elementary school, how literacy in school is an expression of symbolic violence. To this end, we adopted as an instrument of data collection, the Focus Group, the codification of Grounded Theory as a method of data treatment and Content Analysis, based on the analysis unit theme, as a strategy for interpretive analysis of the speeches in the group. Data were analyzed and discussed from the theoretical assumptions of Cultural Studies, the New Literacy Studies, Psychology of Education and sociological concepts of Pierre Bourdieu. The results show that there are symbolic manifestations of violence present in the belief that only the school literacy ensures a superior way of life, social mobility and advancement personnel, the provisions of the naturalization of school culture on the jurisdiction, the values adopted to measureto yourself and others, in the belief that only by school literacy is the ability of a person be considered fully functional and suitable to live in society, the naturalization of the additional effort that the group needs to take to adapt their language to the standard regulated by the school , and in recognition of the superiority of school literacy to other forms of relationship of writing and reading, including your own experiences outside of school. Given this, we reflect on the possibilities of achieving literacy in school proposals that denaturalizes speech settled on beliefs about a culture that, presumably taken as legitimate, is invested with privileges, the visibility and relevance of the multiple literacies that take place, even outside of school.